2022
DOI: 10.1111/josh.13259
|View full text |Cite
|
Sign up to set email alerts
|

The Increasing Utility of School Health Data to Guide Evidence‐Based Interventions

Abstract: T he Centers for Disease Control and Prevention's (CDC) Division of Adolescent and School Health (DASH) works with local decision makers, schools, youth-serving organizations, and parents across the nation to equip youth with knowledge, skills, and resources needed for healthy adolescence and adulthood. Aligned with this effort, DASH maintains high-quality surveillance systems to understand youth health behaviors and assess school health programs and policies. The Youth Risk Behavior Surveillance System (YRBSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…In 2021, YRBS response rates were below 60%, continuing a previously reported decline in YRBS response rates ( 11 ). Whereas a part of the drop in YRBS participation was attributable to school-level COVID-19 safety precautions, disinformation campaigns targeting YRBSs across the country also contribute to declining YRBS response rates ( 17 ). Such campaigns misrepresent survey content, data collection procedures, and data utility.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, YRBS response rates were below 60%, continuing a previously reported decline in YRBS response rates ( 11 ). Whereas a part of the drop in YRBS participation was attributable to school-level COVID-19 safety precautions, disinformation campaigns targeting YRBSs across the country also contribute to declining YRBS response rates ( 17 ). Such campaigns misrepresent survey content, data collection procedures, and data utility.…”
Section: Discussionmentioning
confidence: 99%
“…Profiles data are widely used to monitor school policies and practices at the state and local levels. 3,4 For example, in 2020 alone, 44 states, 28 school districts, 1 territory, and 1 tribe successfully conducted a Profiles survey (principal, lead health education teacher, or both). A recent study found substantial increases in how state, school district, territorial, and tribal programs are using Profiles data to identify professional development needs, plan and monitor programs, support health-related policies and legislation, and seek funding.…”
Section: Implications For School Health Policy Practice and Equitymentioning
confidence: 99%
“…A recent study found substantial increases in how state, school district, territorial, and tribal programs are using Profiles data to identify professional development needs, plan and monitor programs, support health-related policies and legislation, and seek funding. 4 Quality data are critical in identifying disparities in school policies and practices across schools with different characteristics (eg, metropolitan status, region, or socioeconomic status of school families). The ability to reliably measure such policies and practices also is important so that broader federal, state, and local decisions can be made about the equitable distribution of resources dedicated to health education, physical education and physical activity, nutrition services, the school environment, health services, family engagement, and community involvement.…”
Section: Implications For School Health Policy Practice and Equitymentioning
confidence: 99%
See 2 more Smart Citations